(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Satriawan H, Nazirah L, Fitri R, Ernawita. 2022. Evaluation of growth and yield of upland rice varieties under various shading levels and organic fertilizer concentrations. Biodiversitas 23: 2655-2662. The present study aimed to reveal the effect of shading treatments and organic fertilizer dosages on the growth and yield of several upland rice varieties. A split-split plot experimental design with 3 factors was used in this study, consisting of shading levels as the main plot (0%, 30%, 60%), organic fertilizer as a sub-plot (0 g/plant, 25 g/plant, 50 g/plant, and 75 g/plant) and upland rice varieties as sub-sub plot (Ciherang, Situ Bagendit, Kabir 07 and Malaysian upland). Parameters observed were plant height and tiller numbers (expressed as area under the curve), panicle number, dry hay weight, grain weight, flowering time, and chlorophyll number. Results showed that shading treatments significantly affected panicle number, grain weight, and dry hay weight (0% and 30% shade showed the highest result with no significant differences; while 60% shades showed the lowest results); varieties are an important determinant in tiller numbers (Malaysian upland, Ciherang, Situ Bagendit and Kabir 07 with 798.33 ±7.76 and 792.71 ± 9.4, 764.38 ±8.75 and 738.33 ± 14.84, consecutively) and panicle numbers (Ciherang, Situ Bagendit, Malaysian upland and Kabir 07 with 46.51 ± 5.97, 45.26 ±5.68, 44.31 ± 5.09, and 41.08 ± 5.92, consecutively); while organic fertilizer dosages significantly affected tiller numbers in which 26 t ha-1 and 8 t.ha-1 were the highest and the lowest tiller number observed, respectively. Shade and variety interaction significantly affected plant height and flowering time, while interactions of varieties and organic fertilizer dosages are significant on tiller number, panicle number, grain weight, and dry hay weight. The highest total chlorophyll number was shown by Situ Bagendit variety (144.44 granules mm-2) at 60% shading level, while Kabir 07 (98.8 granules mm-2) at 30% shading level showed the lowest total chlorophyll number. It can be concluded that organic fertilization significantly affected the growth and production of upland rice varieties compared to shading treatments. Thus, upland rice cultivation under shading conditions is the potential to be developed, particularly with appropriate rice varieties and optimum organic fertilization techniques.